Analisis dan Desain Pengembangan Media Pembelajaran Power Point Berbasis Literasi Sains untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa - Sulistyaningrum, Heny; Nuraida, Dede; Wardhono, Agus; Andik, Mochamad (FKIP Unirow Tuban, 2023)
Life in the 21st century demands various skills that a person must master in order to become a competent, competitive and successful person in life. known as 21st century skills. One of the 21st century skills that is very important for students is critical thinking skills. The aim of this research is to develop iSpring Suite 8 interactive power point learning media based on scientific literacy to improve students' critical thinking skills. The development of iSpring Suite 8 interactive learning media based on scientific literacy to improve students' critical thinking skills is research and development (R & D) by applying the ADDIE development model which consists of 5 stages, namely analyze, design, develop, implement, and evaluate . The ADDIE model was chosen because of its systematic and interactive structure where the evaluation results of each stage can lead development to the next stage. The results of stage 1 analysis are used as a reference in stage 2 (design). This article examines the results of the learning media development process at stage 1 (analyze) and stage 2 (design).